PRARANCANGAN PABRIK METIL SALISILAT DARI ASAM SALISILAT DAN METANOL DENGAN KAPASITAS 30.000 TON/TAHUN - , TANTIA FATRINA; , Sang Kompiang Wirawan, ST.,MT.,Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Methyl salicylate is one of the most important derivative of salicylic acid, beside aspirin. It is an ester that has a wide range of uses in many industries. In pharmaeutical industries, methyl salicylate is used as an active ingredient in many of itâs formula as an analgesic. Itâs well known aroma has also made it popular in the food beverage and cosmetic industries. Opportunities of developing the methyl salicylate industry in Indonesia is still quite large, considering that there exists no manufacturer here. The plant is planned to operate for 330 days/ year with a 99,65% w/w methyl salicylate production capacity of 30000 tons/ year. The main raw material required is as much as 17909,3043 tons/ year of 99,85% w/w methanol and 31404,0759 tons/ year of salicylic acid. The process used to produce methyl salicylate is the fischer esterification with sulfuric acid catalyst. In general, the methyl salicylate manufacturing process is as follows: (i) reaction between methanol and salicylic acid with sulfuric acid catalyst in a continuous-stirred tank reactor, (ii) neutralization of acid catalyst and residual unreacted salicylic acid using dilute NaOH solution, (iii) separation of salts, (iv) methyl salicylate purification through evaporation and (v) methanol recovery through distillation . As a support, the utility plant unit supplies water as much as 88937,1358 kg/ hour, 560,7322 kVA electricity and compressed air up to 84 m3/ hour. The plant will be established in Kariangau Industrial Complex, Balikpapan, East Kalimantan province, based on availibility of raw material. The region is close to the methanol industry and close to the harbor making it easier to import salicylic acid from China as well as to support distribution of the product. Plant location is close to Wain Dam, so the source of water for the utility plant unit is from river water. Calculation of economic evaluation results in fixed capital as much as $23,470,231.33 and working capital $23,791,896.55. At 100% production rate, ROI before tax 37,23%, ROI after tax 18,61%, POT before tax of 2,1 years, POT after tax of 3,5 years, with BEP at 44,87%, SDP at 24,80%, and 19,19% for DCFRR. Considering the economic evaluation that has been done, this methyl salicylate plant with capacity of 30000 tons / year is worth it to be studied further.